Pilot testing of development wells technology to restore performance - O. G. Semenyaka; S. I. Kushnarov; V. I. Kotsaba; V. B. Volovetskyi; O. M. Shсhyrba (Mechanics and Advanced Technologies)
Issues in focus. The paper deals with a topical issues related to the development of depleted reservoir wells. To develop wells with low reservoir pressures, different technologies are used that involve the use of new equipment.